PENAFSIRAN AL-QURâ€™AN DENGAN FILSAFAT: TELAAH KITAB MAFÄ€TÄªá¸¤ AL-GHAYB FAKHRUDDÄªN AL-RÄ€ZÄª - Zunairoh, Yuyun (IAIN Kediri, 2015)
QurÃ¢â‚¬â„¢anic exegesis has existed since the life of the Prophet Muhammad. It is divided into two forms, i.e. bi almaÃ¢â‚¬â„¢thÃ…Â«rÃ‚Â and bi al-raÃ¢â‚¬â„¢y. Tafsir Falsafi is part of tafsir bil raÃ¢â‚¬â„¢y, which is built upon reasoning when interpretingÃ‚Â the QurÃ¢â‚¬â„¢an. Some scholars reject this interpretation, but some accept it. Tafsir Falsafi is to interpret the QurÃ¢â‚¬â„¢anby using philosophical approaches. Among the scholars are al-FarÃ„ÂbÃ„Â«, Ibn SÃ„Â«nÃ„Â, IkhwÃ„Ân al-Ã¡Â¹Â¢afÃ„Â, and FakhruddÃ„Â«nÃ‚Â al-RÃ„ÂzÃ„Â«. This paper will study FakhruddÃ„Â«n al-RÃ„ÂzÃ„Â«, one of the most leading scholars in the subject, by focusingÃ‚Â on his great work the MafÃ„ÂtÃ„Â«Ã¡Â¸Â¥ al-Ghayb. This paper will examine a method of interpretation of al-RÃ„ÂzÃ„Â«, whichÃ‚Â is taÃ¡Â¸Â¥lÃ„Â«lÃ„Â«.Keywords: Tafsir Falsafi, MafÃ„ÂtÃ„Â«Ã¡Â¸Â¥ al-Ghayb, FakhruddÃ„Â«n al-RÃ„ÂzÃ„Â«